Analisis Elemen Fasad Bangunan dalam Membentuk Sense of Place: Studi Kasus Kawasan Bosbow Madiun - Tarisa Nurahma; Azkia Avenzoar (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Sense of place is the concept of emotional, social, and cultural attachments formed between individuals and a place. The formation of sense of place is influenced by three factors, namely physical form, image, and activities. Historical buildings, especially cultural heritage, have a high sense of place, especially in their physical form. This research aims to analyze the influence of the physical form of colonial building facades in the Bosbow cultural heritage area of Madiun City in forming a sense of place. The research method used is qualitative-descriptive with the approach of field observation and literature study. The results of this study show that the physical elements of buildings such as roofs, gevels, columns, walls, doors, windows, and other decorations have a role in shaping a sense of place in the form of visual impressions, place identity, and physical comfort. These elements not only represent a beautiful colonial character but also serve as a link between historical values and present-day spatial experiences. So the preservation of physical elements in buildings that have a sense of place value such as historic buildings is very important to strengthen the identity of an area.